Lipid nano-bubble combined with ultrasound for anti-keloids therapy. (2nd January 2018) - Wang, Xiao Qing; Li, Zhou-Na; Wang, Qi-Ming; Jin, Hong-Yan; Gao, Zhonggao; Jin, Zhe-Hu
Abstract: Keloids were characterized by excessive growth of fibrous tissues, and shared several pathological characteristics with cancer. They did put physical and emotional stress on patients in that keloids could badly change appearance of patients. N-(4-hydroxyphenyl) retinamide (4HPR) showed cytotoxic activity on a wide variety of invasive-growth cells. Our work was aim to prepare N-(4-hydroxyphenyl) retinamide-loaded lipid microbubbles (4HPR-LM) combined with ultrasound for anti-keloid therapy. 4HPR-loaded liposomes (4HPR-L) were first prepared by film evaporation method, and then 4HPR-LM were manufactured by mixing 4HPR-L and perfluoropentane (PFP) with ultrasonic cavitation method. The mean particle size and entrapment efficiency 4HPR-LM were 113 nm and 95%, respectively. The anti-keloids activity of 4HPR-LM was assessed with BALB/c nude mice bearing subcutaneous xenograft keloids model. 4HPR-LM, combined with ultrasound, could significantly induce apoptosis of keloid fibroblasts in vitro and inhibited growth of keloids in vivo . Thus, 4HPR-LM could be considered as a promising agent for anti-keloids therapy.